2020
DOI: 10.1007/s10869-020-09719-y
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Social Job Stressors can Foster Employee Well-Being: Introducing the Concept of Social Challenge Stressors

Abstract: In the published article "Social Job Stressors Can Foster Employee Well-Being: Introducing the Concept of Social Challenge Stressors", there was an error in Table 1. The last row concerning cooperation demands should be assigned the row number 10 and not 0. This has been corrected in the original article. In addition, the acknowledgements were missing in the final version of the manuscript. The authors apologize for any inconvenience this may have caused. The acknowledgements should read as follows:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…McGarth (1987) believes that stress is the result of unmet needs, and due to their ability to cope with stress, different individuals have different stress experiences when individuals are in a state of imbalance between demand and capacity. Nowadays, emotional exhaustion, job burnout and job performance are regarded as the results of job stress ( Kern et al, 2021 ). For example, research has found that when employees’ work stress is not properly recognized and handled, it may lead to emotional exhaustion and other problems ( Pines and Maslach, 1978 ; Kern et al, 2021 ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…McGarth (1987) believes that stress is the result of unmet needs, and due to their ability to cope with stress, different individuals have different stress experiences when individuals are in a state of imbalance between demand and capacity. Nowadays, emotional exhaustion, job burnout and job performance are regarded as the results of job stress ( Kern et al, 2021 ). For example, research has found that when employees’ work stress is not properly recognized and handled, it may lead to emotional exhaustion and other problems ( Pines and Maslach, 1978 ; Kern et al, 2021 ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Nowadays, emotional exhaustion, job burnout and job performance are regarded as the results of job stress ( Kern et al, 2021 ). For example, research has found that when employees’ work stress is not properly recognized and handled, it may lead to emotional exhaustion and other problems ( Pines and Maslach, 1978 ; Kern et al, 2021 ). Cavanaugh et al (2000) divided job stressors into challenge and hindrance stressors based on the role of job stressors.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation